Purification, crystallization and preliminary X-ray characterization of a haemagglutinin from the seeds of Jatropha curcas - Nair, Divya N.; Suresh, C. G.; Singh, Desh Deepak (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2011)
The plant Jatropha curcas (Euphorbiaceae) is an important source of biofuel from the inedible oil present in its toxic seeds. The toxicity arises from the presence of curcin, a ribosome-inactivating protein showing haemagglutination activity. In this communication, the purification, crystallization and preliminary X-ray characterization are reported of a small protein isolated from J. curcas seeds with a molecular mass of 10 kDa that agglutinates rabbit erythrocytes. The protein was crystallized using the hanging-drop vapour-diffusion method and also by the microbatch method in 72-well HLA plates, using PEG 8000 as the precipitant in both conditions. X-ray diffraction data collected from the rod-shaped crystals were processed in the orthorhombic space group P212121. The crystals diffracted to 2.8 angstrom resolution at 103 K.
Keywords: haemagglutinins; Jatropha curcas